Armed Therapeutic Viruses – A Disruptive Therapy on the Horizon of Cancer Immunotherapy - Bauzon, Maxine; Hermiston, Terry (Frontiers in Immunology, 2014)
For the past 150 years cancer immunotherapy has been largely a theoretical hope that recently has begun to show potential as a highly impactful treatment for various cancers. In particular the identification and targeting of immune checkpoints has given rise to exciting data suggesting that this strategy has the potential to activate sustained antitumor immunity. It is likely that this approach, like other anti-cancer strategies before it, will benefit from co-administration with an additional therapeutic and that it is this combination therapy that may generate the greatest clinical outcome for the patient. In this regard, Oncolytic viruses are a therapeutic moiety that is well suited to deliver and augment these immune-modulating therapies in a highly targeted and economically advantageous way over current treatment. In this review, we discuss the blockade of immune checkpoints, how oncolytic viruses complement and extend these therapies, and speculate on how this combination will uniquely impact the future of cancer immunotherapy.